Biosynthesis, Quantification and Genetic Diseases of the Smallest Signaling Thiol Metabolite: Hydrogen Sulfide - Joanna Myszkowska; Ilia Derevenkov; Sergei V. Makarov; Ute Spiekerkoetter; Luciana Hannibal (MDPI AG, 2021)
Hydrogen sulfide (H2S) is a gasotransmitter and the smallest signaling thiol metabolite with important roles in human health. The turnover of H2S in humans is mainly governed by enzymes of sulfur amino acid metabolism and also by the microbiome. As is the case with other small signaling molecules, disease-promoting effects of H2S largely depend on its concentration and compartmentalization. Genetic defects that impair the biogenesis and catabolism of H2S have been described; however, a gap in knowledge remains concerning physiological steady-state concentrations of H2S and their direct clinical implications. The small size and considerable reactivity of H2S renders its quantification in biological samples an experimental challenge. A compilation of methods currently employed to quantify H2S in biological specimens is provided in this review. Substantial discrepancy exists in the concentrations of H2S determined by different techniques. Available methodologies permit end-point measurement of H2S concentration, yet no definitive protocol exists for the continuous, real-time measurement of H2S produced by its enzymatic sources. We present a summary of available animal models, monogenic diseases that impair H2S metabolism in humans including structure-function relationships of pathogenic mutations, and discuss possible approaches to overcome current limitations of study.